(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
A total of one hundred and twelve day-old broiler chicks (Amo strains) were used to evaluate carcass traits fed with diets containing graded levels of treated sesame waste and its appropriate level of inclusion in the diet. The experimental birds were randomly allocated to four dietary treatments of 28 birds per treatment and each treatment was replicated four times with seven birds per pen. Results obtained showed that there were significant (P<0.05) differences in terms of weight (g), pluck weight (g), carcass weight (g), intestinal weight (g) and liver weight (%). Non-significant (P<0.05) difference were observed in terms of intestinal length (cm), wing weight (g), thigh weight (g), head & legs (%), gizzard (%), lungs (%), heart (%) liver (%), kidney (%) and spleen (%).